Exploratory and Confirmatory Factor Analyses of Delirium Symptoms in a Sample of Nursing Home Residents. (February 2018) - Moyo, Patience; Huang, Ting-Ying; Simoni-Wastila, Linda; Harrington, Donna
Objective: This study examined the latent constructs of delirium symptoms among nursing home (NH) residents in the United States.Method: Cross-sectional NH assessment data (Minimum Data Set 2.0) from the 2009 Medicare Current Beneficiary Survey were used. Data from two independent, randomly selected subsamples of residents ≥65 years were analyzed using exploratory factor analysis (EFA) and confirmatory factor analysis (CFA).Results: There were 367 and 366 individuals in the EFA and CFA, respectively. Assessment of multiple model fit statistics in CFA indicated that the two-factor structure provided better fit for the data than a one-factor solution. The two factors represented cognitive and behavioral latent constructs as suggested by the related literature. A correlation of .72 between these constructs suggested moderate discriminant validity.Conclusion: This finding emphasizes the importance of health care providers to be attentive to both cognitive and behavioral symptoms when diagnosing, treating, and managing delirium.